Prevalence and Incidence of Bacterial Wilt Disease (Ralstonia syzygii subsp. indonesiensis) on Tomato in Simpang Empat District Karo - Siagian, Debi Candra; Safni, Irda; Lisnawita (Talenta Publisher, 2022)
The major disease known as bacterial wilt, which affects tomato plants in Indonesia, is brought on by Ralstonia syzygii subsp. indonesiensis. In Simpang Empat District, Karo Regency, Indonesia, R. syzygii subsp. indonesiensis causes bacterial withery in tomato plants. The purpose of this study is to map its spread. This study is an experimental one that used the survey method to determine the prevalence of disease, the incidence of disease, and the pathogenic isolation of tomato plants at nine different locations throughout Simpang Empat District. The pathogen was isolated from the sample and identified in the lab as R. syzygii subsp. indonesiensis, according to the results. The outcome of the presence of bacterial wilt brought on by R. syzygii subsp. indonesiensis bacteria with various illness occurrences. At a proportion of disease incidence of 57.07%, Ndokum Siroga Location 1 in the community experienced the most disease.